2013
DOI: 10.1063/1.4818642
|View full text |Cite
|
Sign up to set email alerts
|

The bond energy of ReO+: Guided ion-beam and theoretical studies of the reaction of Re+ (7S) with O2

Abstract: The kinetic-energy dependence of the Re(+) + O2 reaction is examined using guided ion-beam mass spectrometry. The cross section for ReO(+) formation from ground state Re(+) ((7)S) is unusual, exhibiting two endothermic features. The kinetic energy dependence for ReO(+) formation is analyzed to determine D0(Re(+)-O) = 4.82 ± 0.05 eV, with the higher energy feature having a threshold 1.35 ± 0.28 eV higher in energy. This bond energy is consistent with much less precise values determined in the literature. Format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 90 publications
(107 reference statements)
2
37
0
Order By: Relevance
“…30 Similarly, CBS limit extrapolations using correlation consistent basis sets are also lower than the experimental value by 0.2 eV for several transition metal oxide cation BDEs. 91,92 For calculations involving several other ThL + species, it was found that high levels of theory, CCSDT(Q) and multireference configuration interaction (MRCI+Q) calculations, were necessary to reproduce experimental relative energies of the ground and excited states. Specific errors relative to the experimental difference between the ground and first excited state (0.08 eV) were 0.06 eV for CCSD(T), 0.03 eV for CCSDT(Q), and 0.01 5 eV for MRCI+Q.…”
mentioning
confidence: 99%
“…30 Similarly, CBS limit extrapolations using correlation consistent basis sets are also lower than the experimental value by 0.2 eV for several transition metal oxide cation BDEs. 91,92 For calculations involving several other ThL + species, it was found that high levels of theory, CCSDT(Q) and multireference configuration interaction (MRCI+Q) calculations, were necessary to reproduce experimental relative energies of the ground and excited states. Specific errors relative to the experimental difference between the ground and first excited state (0.08 eV) were 0.06 eV for CCSD(T), 0.03 eV for CCSDT(Q), and 0.01 5 eV for MRCI+Q.…”
mentioning
confidence: 99%
“…These results are consistent with GIBMS studies of the 3d (Fisher et al, 1990) and 4d (Chen & Armentrout, 1995; Sievers, Chen, & Armentrout, 1996a) TM + (including the much lower reactivity of Mo + ). Comparable GIBMS results for the 5d TM + , Hf + –Au + , reacting with O 2 are collected in Figure 1 (Armentrout, 2013; Armentrout & Li, 2013; Hinton et al, 2009, 2013; Li et al, 2010; Zhang & Armentrout, 2003a). The results are consistent with those of Bohme in all cases.…”
Section: Reactions With Omentioning
confidence: 86%
“…Cross sections for reactions of O 2 with Hf + (red triangles), Ta + (black circles), W + (green inverted triangles) (Hinton et al, 2009), Re + (blue squares) (Armentrout, 2013), Os + (pink diamonds) (Hinton et al, 2013), Ir + (purple triangles) (Armentrout & Li, 2013), Pt + (red inverted triangles) (Zhang & Armentrout, 2003a), Au + ( 1 S) (yellow circles), and Au + ( 3 D) (yellow triangles) (Li et al, 2010) as measured using GIBMS. The arrow indicates the BDE of O 2 at 5.117 eV.…”
Section: Reactions With Omentioning
confidence: 99%
See 2 more Smart Citations